©1992-1997 The MIT Press. Reproduction by any means strictly prohibited.

1.6 Theorems



theorem Definition. A THEOREM is a sentence that can be proved from the empty set of premises.
Comment. We can assert that a given sentence is a theorem by presenting it as the conclusion of a sequent with nothing to the left of the turnstile.
Example.
Prove |- P & Q->Q & P.
1       (1)     P & Q				A
1       (2)     Q				1 &E
1       (3)     P				1 &E
1       (4)     Q & P				2,3 &I
        (5)     P & Q->Q & P			4 ->I (1)
Comment. Note that in step 5 we discharge assumption 1. Hence, the final conclusion rests on no assumptions.
Exercise 1.7 Prove the following theorems, (i) using primitive rules only and (ii) using primitive rules together with derived rules established in a previous exercise.
T1*
|- P->P				Identity
T2*
|- P v ~P			Excluded Middle
T3
|- ~(P & ~P)			Non-Contradiction
T4
|- P->(Q->P)			Weakening
T5*
|- (P->Q) v (Q->P)		Paradox of Material Implication
T6*
|- P <-> ~~P			Double Negation
T7
|- (P <-> Q) <-> (Q <-> P)
T8*
|- ~(P <-> Q) <-> (~P <-> Q)
T9*
|- ((P->Q)->P)->P		Peirce's Law
T10*
|- (P->Q) v (Q->R)
T11*
|- (P <-> Q) <-> (~ P <-> ~Q)
T12*
|- (~P->Q) & (R->Q) <-> (P->R)->Q
T13*
|- P <-> P & P			& Idempotence
T14*
|- P <-> P v P			v Idempotence
T15
|- (P <-> Q) & (R <-> S)->((P->R) <-> (Q->S))
T16
|- (P <-> Q) & (R <-> S)->(P & R <-> Q & S)
T17*
|- (P <-> Q) & (R <-> S)->(P v R <-> Q v S)
T18
|- (P <-> Q) & (R <-> S)->((P <-> R) <-> (Q <-> S))
T19*
|- (P <-> Q)-> ((R->P) <-> (R->Q)) & ((P->R) <-> (Q->R))
T20
|- (P <-> Q)->(R & P <-> R & Q)
T21*
|- (P <-> Q)->(R v P <-> R v Q)
T22
|- (P <-> Q)->((R <-> P) <-> (R <-> Q))
T23
|- P & (Q <-> R)->(P & Q <-> R)
T24
|- P->(Q->R) <-> ((P->Q)->(P->R))
T25
|- P->(Q->R) <-> Q->(P->R)
T26
|- P->(P->Q) <-> P->Q
T27*
|- (P->Q)->Q <-> (Q->P)->P
T28
|- P->~Q <-> Q->~P
T29
|- ~P->P <-> P
T30*
|- (P & Q) v (R & S) <-> ((P v R) & (P v S)) & ((Q v R) & (Q v S))
T31*
|- (P v Q) & (R v S) <-> ((P & R) v (P & S)) v ((Q & R) v (Q & S))
T32*
|- (P->Q) & (R->S) <-> ((~P & ~R) v (~P & S)) v ((Q & ~R) v (Q & S))
T33
|- (P v ~P) & Q <-> Q
T34
|- (P & ~P) v Q <-> Q
T35
|- P v (~P & Q) <-> P v Q
T36
|- P & (~P v Q) <-> P & Q
T37
|- P <-> P v (P & Q)
T38
|- P <-> P & (P v Q)
T39
|- (P->Q & R)->(P & Q <-> P & R)
theorems as derived rules Comment.We now consider a special case of the use of sequents as derived rules. Since it is the conclusion of a sequent without premises, a theorem or a substitution instance of a theorem can be written as a line of a proof with an empty assumption set. For a theorem to be used this way, it must have been proved already by means of primitive rules alone. The annotation should be the name of the theorem or T# (the theorem's number). If a substitution instance is introduced, the substitution pattern should also be included in the annotation.
Example.
Prove P->Q, ~P->Q |- Q.
1       (1)     P->Q			A
2       (2)     ~P->Q			A
        (3)     P v ~P			T2
1,2     (4)     Q			1,2,3 SimDil
Comment. In the preceding example, the annotation for line 3 gives the number of the theorem introduced. Since this theorem has a name, the annotation `Excluded Middle' would also have been acceptable.
Comment. As with sequent introductions, requiring that theorems first be proved using only primitive rules is unnecessarily restrictive.
Exercise 1.8 Prove the following using either primitive or derived rules from the previous exercises. If you like a challenge, prove them again using primitive rules only.
S54
~P->P -| |- P
S55
P <-> Q -| |- ~((P->Q)->~(Q->P))
S56*
P <-> Q -| |- P v Q->P & Q
S57*
P <-> Q -| |- ~(P v Q) v ~(~P v ~Q)
S58
P <-> Q -| |- ~(P & Q)->~(P v Q)
S59
P <-> Q -| |- ~(~(P & Q) & ~(~P & ~Q))
S60
P v Q->R & ~P , Q v R, ~R |- C
S61
~P <-> Q, P->R, ~R  |- ~Q <-> R
S62
~((P <-> ~Q) <-> R), S->P & (Q & T), R v (P
& S) |- S & K->R & Q
S63*
(P & Q) v (R v S) |- ((P & Q) v R) v S
S64
P & (~Q & ~R), P->(~S->T), ~S->(T <-> R v Q)
|- S
S65
P & ~Q->~R, (~S->~P) <-> ~R |- R <-> Q & (P & ~S)
S66*
P v Q, (Q->R) & (~P v S), Q & R->T |- T v S
S67
P->Q v R, (~Q & S) v (T->~P), ~(~R->~P) |- ~T & Q
S68*
P v Q, P->(R->~S), (~R <-> T)->~P |- S & T->Q
S69*
(P <-> ~Q)->~R, (~P & S) v (Q & T), S v T->R |- Q->P
S70*
~S v (S & R), (S->R)->P |- P
S71*
P v (R v Q), (R->S) & (Q->T), S v T->P v Q, ~P |- Q
S72*
(P->Q)->R, S->(~Q->T) |- R v ~T->(S->R)
S73*
P & Q->R v S |- (P->R) v (Q->S)
S74*
(P->Q) & (R->P), (P v R) & ~(Q & R) |- (P & Q) & ~R
S75*
P & Q->(R v S) & ~(R & S), R & Q->S,
S->((R & Q) v (~R & ~Q)) v ~P |- P->~Q
S76
~(P & ~Q) v ~(~R & ~S), ~S & ~Q, T->(~S->~R & P) |- ~T

[PREV] [NEXT]